A cross sectional study of liver function tests in normal pregnancy during third trimester: a treasure from the past - Singh, Nirpaul; Yousuf, Shagufta; Tali, Showkat H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: During pregnancy, a lot of changes do occur and affect every organ system in the body. Objective of the study was to find out expected variations, if any, in liver function tests (LFT) in normal pregnancy during the third trimester. Methods: A total of 75 women aged between 20 to 35 years were enrolled in the study of which 25 were non-pregnant women (control group) and 50 were pregnant women in their third trimester (study group). Results: In the study group, there were no changes in SGPT, serum albumen and serum globulin values in any of the subjects. However out of 50 subjects, a rise in serum alkaline phosphatase could be demonstrated in as many as 44 (88%) subjects. In 10 (20%) subject Serum Bilirubin was high and in 6 (12%) subjects each a rise in SGOT and fall in Serum Proteins could be demonstrated. Conclusions: Except for a significant change in serum phosphatase levels, there is no significant variation in any of the liver function tests in third trimester of pregnancy.